DEVELOPMENT OF PATTERN DESIGN TO INCREASE THE VALUE OF DAMA KARA FASHION PRODUCT - Luthfiya Rahmi; Putri Merak Jingga Sametto; Setia Galuh Santoso; Arini Arumsari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Topics on the issue of Sustainability are becoming increasingly crucial in the business world, including the fashion industry. The sustainable fashion movement has been echoing louder lately along with the promotion of the Sustainable Development Goals (SDG) by the United Nations (UN). Although currently there are many fashion brands that are engaged in the fast fashion sector, there are also those that do not follow this trend, and instead prioritize social and environmental issues through ethical and sustainable fashion discourse, one of which is Dama Kara. This study aims to determine the ability of autistic children to make motif designs as added value to improve a product that promotes sustainable fashion at Dama Kara. The method chosen in this study is a qualitative method with the Design Thinking approach. Through the strategic skills given to autistic children in expressing ideas and thoughts that are felt, it is assessed that they can be improved and become a benchmark in the development of dama kara motif designs as a reference for future product development. The author concludes that there is no free development in Dama kara regarding the drawing potential of every autistic child. In addition, dama kara has provided special therapy for them to get to know the colors and motifs according to the specified application. Considering that there are still many things that are lacking in the future from this research, the suggestion is to study the design of development motives for autistic children in batik skills that are applied to autistic children to improve skills so that this research can utilize skill-based. learn by making batik artwork.